THE CHANGING STRUCTURE OF WAR IN A CYBER-WORLD AND ITS IMPACT ON THE INTERNATIONAL HUMANITARIAN LAW - ISHMEAL, Mohammed (Cyberpolitik Journal, 2017)
War as a social construct of dominating others to achieve ones interest at the expense of other in a competitive global community is an enigma to resolve in the discourse of International Humanitarian Law. Thus, the salience of the transformations of the structure of war in the midst of the current transition of geopolitics from a unipolar world to a seemingly multi-polar world reverberate the debate of international law within the domain of cyber technological weapons, specifically, International Humanitarian Law. This has raised many questions in the application of international humanitarian law in a world where electromagnet weapons, cyber weapons and high-tech defensive system are developed to counter enemy attack. This paper discuss the changing nature of war in a cyber-world bringing to bear its impact on the International Humanitarian Law. The paper posits that with the fast changes in war strategy and cyber oriented weaponry, an improved sophisticated and inclusive laws with a stronger institutional backing must be developed considering the socio-cultural and technological ideas of countries to increase the level of compliance.